Spiritual formation : following the movements of the spirit - NOUWEN, Henri J. M.; Christensen, Michael J.; Laird, Rebecca (New York : HarperCollins, 2010)
"Henri Nouwen, the world-renowned spiritual guide and counselor, understood the spiritual life as a journey of faith and transformation that is deepened by accountability, community, and relationships. Though he counseled many people during his lifetime, his principles of spiritual direction and formation were never written down. Two of Nouwen's longtime students, Michael Christensen and Rebecca Laird, have taken his famous course in spiritual direction and supplemented it with his unpublished writings to create the definitive series on Nouwen's thoughts on the Christian life. The first book in the series, Spiritual Direction, introduced readers to the core concepts of Nouwen's approach to the spiritual life. Book two, Spiritual Formation, showcases Nouwen's life-long effort to re-construct the five classical stages of spiritual development as movements in the journey of faith. The five classical stages are these: 1. Awakening (our desire) 2. Purgation (purifying our passions) 3. Illumination (of God) 4. Dark Night (of the Soul) 5. Unification (with God) Readings, stories, questions for personal reflection, and guided journal inquiry as articulated by Nouwen will provide readers with an experience in spiritual formation with the well-known author, priest, and guide. The third and final book in the series, Spiritual Discernment, is planned to release in 2012"--
Includes bibliographical references.
Keywords: Spiritual life -- Christianity; Spiritual formation